Web usability as a mechanism for disseminating information on the internet - Carvalho Rabelo Filho, Raimundo (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4183, 2018)
Using the usability principles brings benefits in the dissemination of information in web environments improving users' cognitive processes and linked to responsive web techniques forming interfaces with clearer and more effective interactivity. This paper describes the interlinkages between concepts that corroborate with the previous statement, through the redesign of the site frontend for the master's degree program GESTEC (locus of development of this research). Methodologically, applied research is used with a research-action approach for evaluation and results generation. At the end of the processes of construction of the site, considering the criteria and subsidiary parameters, it is noticed that the new layout enhances the interaction characteristics for the users, simplifying access to information.